A green method for preparing fluorine-free MXene and its application in lithium-sulfur batteries
Fluorine-free MXene materials were prepared by stirring the MAX raw material in room temperature molten salt, and reacting at high temperature and stirring in HCl solution, which solved the problems of environmental pollution and poor F atom design in the prior art, and achieved green preparation and excellent electrochemical performance.
Patent Information
- Application Number
- CN202310582236.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-05-19
AI Technical Summary
In the preparation method of existing MXene materials, etching using concentrated HF or a mixed liquid of HCl and LiF results in environmental pollution and poor F atomic designability on structural surfaces, limiting the application of materials in various fields.
A method of preparing fluorine-free MXene is adopted for green. By adding MAX raw materials to room temperature molten salt and stirring, then reacting at high temperature, stirring in HCl solution and drying in vacuum, obtaining fluorine-free Mn+1XnTx material.
It realizes the green preparation of fluorine-free MXene, with simple process, easy to mass production, uniform product structure and morphology, stable electrochemical performance, simple product treatment after etching, and is suitable for lithium-sulfur batteries and other fields.
Smart Images

Figure CN116588940B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of nanomaterial preparation, and specifically relates to a method for green preparation of fluorine-free MXene and application thereof in lithium-sulfur batteries. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] M n+1 X n T x (M: transition metal element, X: carbon, nitrogen or boron element, T x: The surface functional groups O, F, OH, n = 1, 2, 3) are inorganic transition metal carbon, nitrogen or boride, and the two-dimensional material is mainly obtained by selectively etching the A atomic layer connected by weak forces in the structure by the MAX phase. It has the advantages of large specific surface area, high electronic conductivity and small volume change, making M n+1 X n T x The material has unique advantages and shows great application prospects in various fields, including catalysis, energy storage and hydrogen production.
[0004] Currently, M n+1 X n T x The material is mainly prepared by etching with a mixture of concentrated HF or HCl and LiF. Although this method is relatively common and efficient, the reaction solution contains a large amount of F - It is easy to cause danger and environmental pollution, and the F atoms on its surface are poorly designed, which greatly limits the M n+1 X n T x In recent years, various etching strategies, such as alkaline solution etching, electrochemical etching and molten salt etching, have been reported. Among them, the molten salt method for etching MAX phase has attracted much attention, mainly because this method can effectively regulate the M n+1 X n T xto improve its conductivity and physicochemical properties. For example: Patent 202010359156.4 discloses a method for preparing Mxene materials based on the molten salt method, comprising the following steps: evenly mixing MAX phase ceramics, chloride ion salts or bromide ion salts, NaCl, and KCl spheroidal graphite; etching MAX phase ceramics by molten salt reaction in a crucible, and then ultrasonically cleaning the reaction product in 10% dilute hydrochloric acid, filtering, and drying to obtain a multilayer Mxene material. Among them, NaCl and KCl need to become molten salts under high temperature conditions before the MAX precursor can be immersed and contacted. At the same time, in order to make NaCl and KCl fully contact with the MAX phase, ball milling treatment is adopted, and the process is complicated. In addition, only a small amount of molten salt has good physical (melting point and boiling point) and chemical properties (redox potential) to etch the MAX phase, and the contact between the molten salt and the MAX phase is poor, resulting in uneven MAX etching, which affects the properties of the surface functional groups and their electrochemical properties, limiting the fluorine-free M n+1 X n T x development. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a method for green preparation of fluorine-free MXene and application thereof in lithium-sulfur batteries.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention provides a method for green preparation of fluorine-free MXene, comprising:
[0008] Adding the MAX raw material into room temperature molten salt, stirring at 25 to 80° C. for 12 to 100 hours, to obtain a first mixed solution;
[0009] placing the first mixed solution at 300-750° C. to react and obtain a black powder;
[0010] The black powder is placed in an HCl solution and stirred for 12 to 48 hours to obtain a second mixed solution, and the second mixed solution is filtered and vacuum dried to obtain a black powder M n+1 X n T x ;
[0011] The room temperature molten salt is 1-butyl-3-methyl-1H-imidazol-3-ium tetrachloroferrate, 1-butyl-3-methylimidazolium chloride or 1-butyl-3-methyl-1H-imidazol-3-ium hexafluoroantimonate.
[0012] The second aspect of the present invention provides a fluorine-free M prepared by the above method. n+1 X n Tx Material.
[0013] The third aspect of the present invention provides a separator for a lithium-sulfur battery, comprising:
[0014] The above fluorine-free M n+1 X n T x The material, Super P and PVDF are mixed and fully ground, and then NMP is added to make a uniform slurry;
[0015] The slurry is evenly coated on one side of a polypropylene (PP) diaphragm to obtain the product.
[0016] The fourth aspect of the present invention provides the above-mentioned fluorine-free M n+1 X n T x Application of materials in the field of energy storage.
[0017] Beneficial effects of the present invention
[0018] (1) The present invention is easy to operate, has a simple process setting, and the precursors used are all commercial materials. The preparation process is simple, easy to mass produce, and is expected to be commercialized. Compared with chloride ion salts or bromide ion salts, the molten salt used in the present invention is in a liquid state at room temperature, which can better immerse the MAX precursor, the etching effect is more thorough, the structure and morphology of the product are more uniform, the electrochemical performance is more stable, and the treatment of the etched product is simpler; at the same time, no ball milling process is required, making the etching process simpler, easy to operate and energy-saving.
[0019] (2) The present invention changes the contact state between the room temperature molten salt and the MAX phase by regulating the temperature and time of stirring the mixed solution in step 1;
[0020] (3) The present invention can adjust M by regulating the heating rate, reaction time and reaction temperature in step 2. n+1 X n T x The layered structure;
[0021] (4) The present invention can adjust M by regulating the temperature of vacuum drying in step 3. n+1 X n T x The aggregation state and chemical composition of the surface structure.
[0022] (5) Currently, M n+1 X n T xThe modified lithium-sulfur battery separator has different effects on inhibiting the shuttling of polysulfides and improving the electrochemical performance of the battery. When the MXene prepared by the present invention is used in a lithium-sulfur battery, it has good inhibition of the shuttling of polysulfides and excellent electrochemical performance, providing a green way of preparing MXene. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention, and do not constitute improper limitations on the present invention.
[0024] Figure 1 M in Example 1 n+1 X n T x XRD pattern of .
[0025] Figure 2 M in Example 1 n+1 X n T x SEM image of .
[0026] Figure 3 M in Example 1 n+1 X n T x SEM image of the modified membrane.
[0027] Figure 4 M in Example 1 n+1 X n T x Cross-sectional SEM image of the modified separator.
[0028] Figure 5 M in Example 1 n+1 X n T x Cyclic voltammogram of the modified separator used in lithium-sulfur battery.
[0029] Figure 6 M in Example 1 n+1 X n T x And the cycling performance diagram of the comparative modified separator for lithium-sulfur batteries. DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0031] Explanation of terms
[0032] In the present invention, MXene is a two-dimensional material, Mn +1 X n T x This is a common naming method.
[0033] "Room temperature molten salt" is a proprietary name for a class of substances, which refers to: a class of substances composed entirely of ions and are in liquid state at or near room temperature.
[0034] As introduced in the background technology, in view of the deficiencies in the prior art, the present invention proposes a green method for preparing fluorine-free MXene, MXene prepared by the method and its application in the battery field.
[0035] A method for green preparation of fluorine-free MXene, specifically comprising:
[0036] Adding the MAX raw material into room temperature molten salt, stirring at 25 to 80° C. for 12 to 100 hours, to obtain a first mixed solution;
[0037] placing the first mixed solution at 300-750° C. to react and obtain a black powder;
[0038] The black powder is placed in an HCl solution and stirred for 12 to 48 hours to obtain a second mixed solution, and the second mixed solution is filtered and vacuum dried to obtain a black powder M n+1 X n T x ;
[0039] The molten salt is 1-butyl-3-methyl-1H-imidazol-3-ium tetrachloroferrate, 1-butyl-3-methylimidazolium chloride or 1-butyl-3-methyl-1H-imidazol-3-ium hexafluoroantimonate.
[0040] In some embodiments, the MAX raw material is one or more of Ti3AlC2, Ti2AlC, Nb2AlC, V2AlC, and MoAlB.
[0041] In some embodiments, the first mixed solution is placed at 300-750° C. and the reaction time is 24-48 hours.
[0042] In some embodiments, the first mixed solution is placed at 300-750° C. with a heating rate of 1-4° C. / min.
[0043] In some embodiments, the HCl concentration is 0.5-2M.
[0044] In some embodiments, the black powder is placed in the HCl solution and stirred for 24 h to 36 h.
[0045] In some embodiments, the vacuum drying temperature is 50-60°C.
[0046] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0047] Example 1
[0048] A green preparation of fluorine-free Ti3C2T x Materials methods, including:
[0049] (1) Add 0.25 g Ti3AlC2 to 5 ml 1-butyl-3-methyl-1H-imidazol-3-ium tetrachloroferrate and stir at room temperature for 24 h. Then transfer it to a tube furnace and heat it to 550°C at a rate of 4°C / min and keep it for 24 h. After cooling naturally, add the obtained solid to 1 M hydrochloric acid and stir for 24 h. Then, vacuum filter to obtain a black powder. Place it in a vacuum drying oven and dry it at 50°C. Figure 1 Ti3C2T x The XRD pattern of Ti3C2T x The etched samples were successfully etched, and the broad peak at 20-30° was considered to be amorphous carbon. The carbon mainly originated from the decomposition of imidazole in the structure of room temperature molten salt. Figure 2 Ti3C2T x The SEM image shows that the two-dimensional layered structure is consistent with the reported MXene structure.
[0050] (2) 80 mg Ti3C2T x 10 mg Super P and 10 mg PVDF were mixed and ground thoroughly, and then 0.5 ml NMP was added to make a uniform slurry. After that, the prepared slurry was evenly coated on one side of a polypropylene PP separator (Celgard2500) and placed in a vacuum drying oven at 60 ° C for 12 h to obtain Ti3C2T x @PP composite film. Figure 3 The SEM image of the composite film shows that Ti3C2T x @PP composite film. Figure 4 This is a cross-sectional SEM image of the composite membrane, and its thickness is about 10 μm.
[0051] (3) Ti3C2T x @PP composite film is used as the separator of lithium-sulfur battery, 1.0M lithium bis(trifluoromethanesulfonyl)imide as electrolyte, lithium foil as counter electrode and S / ketjen black as positive electrode, assembled into button cell, and its cyclic voltammetry curve and cycle performance. Figure 5The cyclic voltammetry curve of the lithium-sulfur battery is shown in the voltage window of 1.8-2.8V. The reduction peaks at 2.3 and 2.05V are from S8 to Li2S. n (4≤n≤8) and Li2S n to Li2S2 / Li2S, and the oxidation peak at 2.32 V is the conversion process from Li2S2 / Li2S to Li2S n and S8 transformation process. Figure 6 For lithium-sulfur batteries at 0.2C (1C = 1675mA g -1 ) under the cycle performance, the specific capacity after 80 cycles is about 750mA hg -1 .
[0052] Example 2
[0053] (1) Add 0.25 g Ti3AlC2 to 5 ml 1-butyl-3-methyl-1H-imidazol-3-ium hexafluoroantimonate and stir at room temperature for 24 h. Then transfer it to a tube furnace and heat it to 550 °C at a rate of 4 °C / min and keep it for 24 h. After cooling naturally, add the obtained solid to 1 M hydrochloric acid and stir for 24 h. Then, vacuum filter to obtain a black powder. Place it in a vacuum drying oven and dry it at 50 °C.
[0054] (2) 80 mg Ti3C2T x 10 mg Super P and 10 mg PVDF were mixed and ground thoroughly, and then 0.5 ml NMP was added to make a uniform slurry. After that, the prepared slurry was evenly coated on one side of a polypropylene PP separator (Celgard2500) and placed in a vacuum drying oven at 60 ° C for 12 h to obtain Ti3C2T x @PP composite film.
[0055] (3) Ti3C2T x The PP composite film was used as the separator of the lithium-sulfur battery, 1.0M lithium bis(trifluoromethanesulfonyl)imide as the electrolyte, lithium foil as the counter electrode and S / ketjen black as the positive electrode to assemble into a button cell, and its cycling performance at a current density of 0.2C was 812 mA hg -1 .
[0056] Example 3
[0057] (1) 0.25 g Ti3AlC2 was added to 5 ml 1-butyl-3-methylimidazolium chloride and stirred at room temperature for 24 h. The mixture was then transferred to a tube furnace and heated to 550 °C at a rate of 4 °C / min and maintained for 24 h. After cooling naturally, the obtained solid was added to 1 M hydrochloric acid and stirred for 24 h. A black powder was obtained by vacuum filtration. The powder was placed in a vacuum drying oven and dried at 50 °C.
[0058] (2) 80 mg Ti3C2T x 10 mg Super P and 10 mg PVDF were mixed and ground thoroughly, and then 0.5 ml NMP was added to make a uniform slurry. After that, the prepared slurry was evenly coated on one side of a polypropylene PP separator (Celgard2500) and placed in a vacuum drying oven at 60 ° C for 12 h to obtain Ti3C2T x @PP composite film.
[0059] (3) Ti3C2T x The PP composite film is used as the separator of the lithium-sulfur battery, 1.0M lithium bis(trifluoromethanesulfonyl)imide is used as the electrolyte, lithium foil is used as the counter electrode, and S / ketjen black is used as the positive electrode to assemble the button cell. The cycle performance at the current density of 0.2C is 680mA hg -1 .
[0060] Example 4
[0061] (1) 0.25 g Ti2AlC was added to 5 ml 0.5 M hydrochloric acid solution and stirred at room temperature for 24 h. Then, it was transferred to a tube furnace and heated to 550 °C at a rate of 4 °C / min and maintained for 24 h. After natural cooling, the obtained solid was added to 1 M hydrochloric acid and stirred for 24 h. Black powder was obtained by vacuum filtration. It was placed in a vacuum drying oven and dried at 50 °C.
[0062] (2) 80 mg Ti2CT x 10 mg Super P and 10 mg PVDF were mixed and ground thoroughly, and then 0.5 ml NMP was added to make a uniform slurry. After that, the prepared slurry was evenly coated on one side of a polypropylene PP diaphragm (Celgard2500) and placed in a vacuum drying oven at 60 ° C for 12 h to obtain Ti2CT x @PP composite film.
[0063] (3) Ti2CT xThe PP composite film is used as the separator of the lithium-sulfur battery, 1.0M lithium bis(trifluoromethanesulfonyl)imide is used as the electrolyte, lithium foil is used as the counter electrode, and S / ketjen black is used as the positive electrode to assemble the button cell. The cycle performance at the current density of 0.2C is 653mA hg -1 .
[0064] It can be seen that the use of 0.5M hydrochloric acid solution can remove a small amount of oxides generated during the high-temperature reaction.
[0065] Example 5
[0066] (1) 0.25 g of Nb2AlC was added to 5 ml of 1-butyl-3-methyl-1H-imidazol-3-ium tetrachloroferrate and stirred at 80°C for 24 h. The mixture was then transferred to a tube furnace and heated to 550°C at a rate of 4°C / min and maintained for 24 h. After cooling naturally, the obtained solid was added to 2M hydrochloric acid and stirred for 24 h. A black powder was obtained by vacuum filtration. The powder was placed in a vacuum drying oven and dried at 50°C.
[0067] (2) 80mgNb2CT x , 10 mg Super P and 10 mg PVDF were mixed and ground thoroughly, and then 0.5 ml NMP was added to make a uniform slurry. After that, the prepared slurry was evenly coated on one side of a polypropylene PP separator (Celgard2500) and placed in a vacuum drying oven at 60 ° C for 12 hours to obtain Nb2CT x @PP composite film.
[0068] (3) Nb2CT x The PP composite film is used as the separator of the lithium-sulfur battery, 1.0M lithium bis(trifluoromethanesulfonyl)imide is used as the electrolyte, lithium foil is used as the counter electrode, and S / ketjen black is used as the positive electrode to assemble the button cell. The cycle performance at the current density of 0.2C is 547mA hg -1 .
[0069] It can be seen from this that stirring at 80°C allows room temperature molten salt to better contact with MAX, providing a basis for obtaining more complete etching of MXene at high temperature.
[0070] Example 6
[0071] (1) Add 0.25 g of V2AlC to 5 ml of 1-butyl-3-methyl-1H-imidazol-3-ium tetrachloroferrate and stir at 50°C for 24 h. Then transfer it to a tube furnace and heat it to 550°C at a rate of 4°C / min and keep it for 24 h. After cooling naturally, add the obtained solid to 2M hydrochloric acid and stir it for 24 h. Then, vacuum filter it to obtain a black powder. Place it in a vacuum drying oven and dry it at 50°C.
[0072] (2) 80 mg V2CT x 10 mg Super P and 10 mg PVDF were mixed and ground thoroughly, and then 0.5 ml NMP was added to make a uniform slurry. After that, the prepared slurry was evenly coated on one side of a polypropylene PP diaphragm (Celgard2500) and placed in a vacuum drying oven at 60°C for 12 hours to obtain V2CT x @PP composite film.
[0073] (3) V2CT x The PP composite film was used as the separator of the lithium-sulfur battery, 1.0M lithium bis(trifluoromethanesulfonyl)imide as the electrolyte, lithium foil as the counter electrode and S / ketjen black as the positive electrode to assemble into a button cell, and its cycle performance at a current density of 0.2C was 601mA hg -1 .
[0074] It can be seen that stirring at 50°C allows room temperature molten salt to better contact with MAX, providing a basis for obtaining more complete etching of MXene at high temperature.
[0075] Example 7
[0076] (1) Add 0.25 g of MoAlB to 5 ml of 1-butyl-3-methyl-1H-imidazol-3-ium tetrachloroferrate and stir at room temperature for 24 h. Then transfer it to a tube furnace and heat it to 550°C at a rate of 4°C / min and keep it for 24 h. After cooling naturally, add the obtained solid to 1 M hydrochloric acid and stir it for 24 h. Then, vacuum filter it to obtain a black powder. Place it in a vacuum drying oven and dry it at 50°C.
[0077] (2) 80 mg MoBT x 10 mg Super P and 10 mg PVDF were mixed and ground thoroughly, and then 0.5 ml NMP was added to make a uniform slurry. After that, the prepared slurry was evenly coated on one side of a polypropylene PP separator (Celgard2500) and placed in a vacuum drying oven at 60°C for 12 hours to obtain MoBT. x @PP composite film.
[0078] (3)MoBT x The PP composite film was used as the separator of the lithium-sulfur battery, 1.0M lithium bis(trifluoromethanesulfonyl)imide as the electrolyte, lithium foil as the counter electrode and S / ketjen black as the positive electrode to assemble into a button cell, and its cycling performance at a current density of 0.2C was 827 mA h g -1 .
[0079] It can be seen from this that stirring at 50°C is only to allow the molecules in the room temperature molten salt to better enter the structure of MAX, improve the contact between the two, and provide conditions for obtaining more complete etching of MXene at high temperature.
[0080] Comparative Example 1
[0081] The difference from Example 1 is that 1-butyl-3-methyl-1H-imidazol-3-ium tetrachloroferrate is not added. The cycle performance at a current density of 0.2C is 510 mA h g -1 ,like Figure 6 shown.
[0082] Comparative Example 2
[0083] The difference from Example 1 is that 10 g MAX phase precursor, 6 g CuCl2, 7.8 g NaCl and 9.9 g KCl are ball-milled and mixed (the solution of Example 1 of Patent 202010359156.4), and its cycle performance at a current density of 0.2C is 538 mA hg -1 ,like Figure 6 shown.
[0084] From the comparison between Example 1 and Comparative Examples 1 and 2, it can be seen that the room temperature molten salt used in the present invention can better immerse the MAX precursor, the etching effect is more thorough, the structure and morphology of the product are more uniform, and the MAX prepared by the present invention is n+1 X n T x The modified lithium-sulfur battery separator has a good effect on inhibiting the shuttling of polysulfides and improving the electrochemical performance of the battery.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A green method for preparing fluorine-free MXene, characterized in that: include: Adding the MAX raw material into room temperature molten salt, stirring at 25-80° C. for 12-100 hours, to obtain a first mixed solution; placing the first mixed solution at 300-750° C. to react and obtain a black powder; The black powder is placed in an HCl solution and stirred for 12 to 48 hours to obtain a second mixed solution, and the second mixed solution is filtered and vacuum dried to obtain a black powder M. n+1 X n T x ; The room temperature molten salt is 1-butyl-3-methyl-1H-imidazol-3-ium tetrachloroferrate or 1-butyl-3-methylimidazolium chloride.
2. The green method for preparing fluorine-free MXene according to claim 1, characterized in that: The MAX raw material is one or more of Ti3AlC2, Ti2AlC, Nb2AlC, and V2AlC.
3. The green method for preparing fluorine-free MXene according to claim 1, characterized in that: The first mixed solution is placed at 300-750° C. and the reaction time is 24-48 hours.
4. The green method for preparing fluorine-free MXene according to claim 1, characterized in that: The first mixed solution is placed at 300-750° C., with a heating rate of 1-4° C. / min.
5. The green method for preparing fluorine-free MXene according to claim 1, characterized in that: The HCl concentration is 0.5-2M.
6. The green method for preparing fluorine-free MXene according to claim 1, characterized in that: The black powder is placed in the HCl solution and stirred for 24 h to 36 h.
7. The green method for preparing fluorine-free MXene according to claim 1, characterized in that: The vacuum drying temperature is 50-60°C.
8. Fluorine-free M prepared by the method described in any one of claims 1 to 7 n+1 X n T x Material.
9. A separator for a lithium-sulfur battery, characterized in that: include: The fluorine-free M according to claim 8 n+1 X n T x The material, Super P and PVDF are mixed and fully ground, and then NMP is added to make a uniform slurry; The slurry is evenly coated on one side of a polypropylene (PP) diaphragm to obtain the product.
10. The fluorine-free M according to claim 8 n+1 X n T x Application of materials in the field of energy storage.
Citation Information
Patent Citations
Method for preparing Mxene material based on molten salt method
CN111403186A
Method for preparing MXene material
CN112794328A
Preparation method of modified MXene material with sulfonic group
CN113042078A
Cited By
MXene fluoride-free etching method based on supercritical and supercritical puffing stripping technologies
CN121974352A